“A Comparative Analysis of the Number of Organ Retrievals in Relation to Potential Donation Qualifications in Populations of Patients From a Single Anesthesiology and Intensive Care Unit in 2017-2018” - Kudliński, Bartosz; Trosiak, Marta; Wojciech, Magdalena; Zaborniak, Gabriel; Kania, Jagoda; Buczek, Aleksandra; Fedorowicz, Olga; Myślak, Marek (Frontiers in Medicine, 2022)
The population of patients declared as brain dead and qualified for organ donation is relatively low in Poland. The main causes of brain death include cerebral vascular diseases and brain trauma (54% and 34% respectively, according to Poltransplant registry data). The number of or-gan procurements in Poland is constantly recorded on average at 14 donations per 1 million citi-zens (14/mln) in 2017 and 12 donations per one million in 2018. It is difficult to precisely define the number of patients who meet the criteria for brain death certification. The authors have retro-spectively analyzed the medical data of 229 patients from 2017 and 2018 records with the aim of identifying potential organ donors among patients of the Intensive Care Unit (ICU) in the Univer-sity Hospital in Western Poland. Brain death was suspected in 53 patients (23.14%). Brain imag-ing to confirm no cerebral flow (which is consistent with brain death) was performed in 17 pa-tients (7.45%) and this, as a result, led to organ donation in 9 cases (3.93%). The factors identified as having a positive influence on organ donation included: daily thorough physical examination, (Glasgow Coma Scale) GCS assessment, depth and duration of sedation, ICU length of stay and early performance of a CT-angiogram.